A Methodology for Adaptive Competence Assessment and Learning Path Creation in ISAC - Nussbaumer, A.; Guetl, Christian; Neuper, W. (Kassel University Press, 2010)
In this paper a technique is presented how to realise adaptive competence assessment and the creation of adaptive learning paths for the ISAC system. ISAC is an intelligent tutoring system which supports the learner in solving problems in applied mathematics. It is able to monitor and support the learner in each calculation step. However, it does not support building user and competence profiles and sequencing of problems and learning objects based on the personal needs. Therefore, a technique has been developed and integrated with ISAC, which allows for assessing the competence profile of learners and creating learning paths adaptively based on the assessed competences. Development has been done in a modular way which also provides other features such as goal setting and visual feedback of skill gaps and progress.